Factors affecting surgical outcomes in cervical spondylotic myelopathy - Nair, Anand P.; Abraham, Tinu Ravi; Erubothu, Alekhya (International Surgery Journal, 2025)
Background: Cervical spondylotic myelopathy (CSM) is the most common cause of spinal cord dysfunction in adults over 40 years. It is often progressive, and delayed diagnosis may result in irreversible disability. Surgical decompression is the primary treatment modality in moderate to severe cases. This study evaluated clinical and radiological prognostic factors influencing postoperative recovery in CSM. Methods: A prospective observational study was conducted between February 2023 and February 2024 in the department of neurosurgery, government medical college Kottayam. A total of 85 patients undergoing anterior or posterior decompression surgery for CSM were included. Clinical outcomes were assessed using Nurick’s grade and the modified Japanese orthopaedic association (mJOA) scale (Benzel’s modification). Radiological parameters including effective canal diameter and intramedullary signal changes on T2-weighted MRI were studied. Statistical analysis (ANOVA, chi-square) was used to correlate factors with outcomes. Results: Better outcomes were associated with younger age (<40 years), symptom duration <1 year, Nurick grade 0-2, single-level compression, effective canal diameter >11 mm, and absence of T2 hyperintensity. Poor prognosis was linked to age >60 years, symptoms >2 years, higher Nurick grade (four to five), multilevel compression, canal diameter <9 mm, and well-defined T2 signal changes. The newly developed prognostic scoring system showed good correlation with outcomes. Conclusions: Early diagnosis and timely surgical intervention significantly improve functional outcomes in CSM. Age, symptom duration, preoperative disability, canal diameter, and intramedullary MRI changes are key prognostic indicators. The proposed prognostic scale may aid in clinical decision-making.